2010
DOI: 10.25225/fozo.v59.i3.a6.2010
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Study of Polyandrous Spawning inBlicca bjoerknaUnder a Controlled Environment

Abstract: This study describes the reproductive behaviour of silver bream, Blicca bjoerkna, in an aquarium environment with hormonal injection, constant temperature and natural photoperiod conditions. The results revealed that the reproductive behaviour of silver bream was polyandrous with courting tactics including a high level of tactile stimulation and following behaviour developed by the males, but without territorial or aggressive acts. The individual participation of males in mating acts showed a significant posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Importantly for this study, all three species are reproductively sympatric because they (1) can inhabit the same water body (Holopainen & Pitkänen, 1985; Holopainen et al , 1997; Brunberg & Blomqvist, 1998), (2) have overlapping spring spawning seasons and (3) spawn in similar shallow water habitats where untended, adhesive eggs are broadcast among the roots and leaves of aquatic vegetation (Breder & Rosen, 1966; Holčik, 1967; Aho & Holopainen, 2000; Kottelat & Freyhof, 2007). Furthermore, these species all employ a polygynandrous mating system common to cyprinids in which multiple males vigorously compete for spawning position for the brief period of several hours during which ovulated eggs are fertile (Breder & Rosen, 1966; Kottelat & Freyhof, 2007; Poncin et al , 2010). Although reproductive sympatry and similar spawning habits probably account for the fact that B. bjoerkna and S. erythrophthalmus hybridize with each other and other leuciscins (Gasowska, 1968; Nzau Matondo et al , 2008, 2009), it is not known if they hybridize with C. carassius .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly for this study, all three species are reproductively sympatric because they (1) can inhabit the same water body (Holopainen & Pitkänen, 1985; Holopainen et al , 1997; Brunberg & Blomqvist, 1998), (2) have overlapping spring spawning seasons and (3) spawn in similar shallow water habitats where untended, adhesive eggs are broadcast among the roots and leaves of aquatic vegetation (Breder & Rosen, 1966; Holčik, 1967; Aho & Holopainen, 2000; Kottelat & Freyhof, 2007). Furthermore, these species all employ a polygynandrous mating system common to cyprinids in which multiple males vigorously compete for spawning position for the brief period of several hours during which ovulated eggs are fertile (Breder & Rosen, 1966; Kottelat & Freyhof, 2007; Poncin et al , 2010). Although reproductive sympatry and similar spawning habits probably account for the fact that B. bjoerkna and S. erythrophthalmus hybridize with each other and other leuciscins (Gasowska, 1968; Nzau Matondo et al , 2008, 2009), it is not known if they hybridize with C. carassius .…”
Section: Introductionmentioning
confidence: 99%
“…The mating combination of the female hybrid and its three corresponding males most frequently observed, indicates that these hybrids have a polyandrous mating system which could give as in no hybrids fish species many advantages useful for the survival of offspring such as high fertility, prevention of inbreeding and maintenance genetic diversity (Kellogg et al, 1998;Arnqvist and Nilsson, 2000;Becher and Magurran, 2004;Ivy and Sakaluk, 2005). This mating system corresponds to that of the parental species (Svardson, 1949;Poncin et al, 2010) and other no hybrids fish species belonging to the Cyprinidae family and other families (Goto, 1987;Kodric-Brown, 1995;Maclnnis and Corkum, 2000).…”
Section: Spawning Behaviourmentioning
confidence: 99%
“…Poncin et al (2010) have observed males of silver bream expressing a high level of courtship with numerous tactile stimulations of the female during the spawning period. Several authors have reported that these two fish species exhibit non-aggressive and non-territorial tactics during the breeding season (Svardson, 1949;Spivak, 1987;Haberlehner, 1988;Poncin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…White bream is a multiple spawner (Brylińska andŻbikowska 1997, Lefl er et al 2008). The available studies of the species consider its reproductive behaviour (Poncin et al 2010), hormonal oogenesis regulation (Rinchard and Kestemont 2003), analysis of gonads from selected months (Kopiejewska and Kozłowski 2007), as well as the full-year gonad development cycle only in females, but under ambient thermal conditions Kestemont 1996, Lefl er et al 2008). A broad analysis of ecological conditions favourable for the reproduction of white bream has also been conducted (Janáč et al 2010).…”
Section: Introductionmentioning
confidence: 99%